A case study of grinding coarse 5 mm particles into sand grade particles less than 2.36 mm - Reed, Aaron; Koroznikova, Larissa; Khandelwal, Manoj (Vietnam Journal of Earth Sciences, 2020)
This paper presents the viability study of utilising a rod or ball mill to grind a ‘5 mm grit’ to 100% passing 2.36 mm and fit in with a desired particle size analysis. The aim is to introduce this grit into the concrete grade sand produced at the Hanson owned Axedale Sand & Gravel quarry to reduce generated waste and improve the process efficiency. A ball mill and rod mill were used to grind the samples at an interval of 5 and 10 minutes. From the laboratory experimental analysis, it was found that a ball mill with 5 minutes grinding time in closed-circuit using a classifier to remove undersize and reintroduce oversize to the mill would be a viable option in an industrial setting. A Bond Ball Mill Grindability Test was undertaken to determine the grindability of the 5 mm grit, which served to determine the power (kWh/t) required to grind it to 100% passing 2.36 mm. The bond ball mill grindability test showed that the grit had a work index value of 17.66 kWh/t. This work index gives an actual work input of 13.54 kWh/t, meaning that for every ton of feed material introduced to the mill, 13.54 kWh of work input is required to grind it to 150 microns.